Time evolution of a pumped molecular magnet—A time-resolved inelastic neutron scattering study - T. R. Reeder; Paraj Titum; J. Kindervater; V. J. Stewart; Q. Ye; J. A. Rodriguez-Rivera; Y. Qiu; N. Maliszewskyj; T. M. McQueen; C. L. Broholm (Proceedings of the National Academy of Sciences, 2025)
Introducing an experimental technique of time-resolved inelastic neutron scattering (TRINS), we explore the time-dependent effects of resonant pulsed microwaves on the molecular magnet Cr 8 F 8 Piv 16 . The octagonal rings of magnetic Cr 3+ atoms with antiferromagnetic interactions form a singlet ground state with a weakly split triplet of excitations at 0.8 meV. A 4.6 tesla field was applied to tune the splitting between two members of the triplet excited level | 1 ⟩ ↔ | 2 ⟩ to resonance with 105 GHz (0.434 meV) microwaves. The time-dependent occupations of the ground state | 0 ⟩ , lower lying levels | 1 ⟩ and | 2 ⟩ , and higher energy states | λ ≥ 3 ⟩ were extracted during and after 20 s long microwave pulses incident along the (101) direction of a Cr 8 F 8 Piv 16 crystal held at 1.9 K. At significantly elevated spin temperatures, we found underpopulation relative to thermal equilibrium of | 2 ⟩ and spin-lattice thermalization time scales ranging from 1.6(2) s to 5.7(2) s depending on the power level. This contrasts with the relaxation time τ 1 ( T → 0 ) = 27 ( 5 ) μ s inferred for | 2 ⟩ from in situ Electron Spin Resonance measurements. By probing a broad range of excited states during intense microwave pumping, TRINS thus provides a first view of long lived excited states in a molecular antiferromagnet.